Abscesses and fistula orginated or disseminated above the levator ani. - Bermúdez Villegas, Jorge; Veirano, Gustavo; Rompani, Omar (Cirugía del Uruguay, 1988)
fistula located originally or secondarily above the levator ani. They point out the relative frequency of 10.6% in the series as well as the association with rectum neoplasm in five cases and with colon neoplasm in one case.